Self‐ and other‐evaluative moral emotions in prosocial contexts: A comparison of Chinese and Canadian adolescents. Issue 2 (10th January 2019) - Jia, Fanli; Li, Lihong; Krettenauer, Tobias
Abstract: This study investigated adolescents' self‐ and other‐evaluative moral emotions in prosocial contexts across cultures (Chinese and Canadian). The sample consisted of 341 adolescents from three age groups: early adolescents (Grade 7–8), middle adolescents (Grade 10–11), and late adolescents (1st–2nd‐year university). Approximately equal numbers of participants were recruited across genders, age groups, and cultures. Participants were presented eight different scenarios depicting the self or others in prosocial contexts. Moral emotions were assessed following each scenario by asking participants to rate the intensity of both self‐evaluative (pride, satisfaction, guilt, and shame) and other‐evaluative (admiration, respect, anger, and contempt) moral emotions. The results indicated that Chinese early adolescents rated more intense other‐evaluative emotions than the same age group in Canada. Chinese middle and late adolescents rated less intense self‐evaluative emotions than the same age groups in Canada. Overall, the results revealed both cultural differences and similarities in self‐ and other‐evaluative moral emotions. The present study also suggests a cross‐cultural investigation of moral emotion from a developmental perspective.